STRATEGI KOMUNIKASI PT. SEATAP TEKNOLOGI BERKARYA DALAM MEMBANGUN BRANDING DI MEDIA SOSIAL INSTAGRAM - Nugraha, Agung; Soegoto, Eddy Soeryanto; Wahdiniwaty, Rahma; Bachtiar, Adam Mukharil; Sumitra, Irfan Dwiguna (Universitas Komputer Indonesia, 2025)
This study examines the communication strategies implemented by PT. Seatap Teknologi Berkarya in building brand identity through the Instagram platform. As a wedding planning company established in 2018, Instagram serves as its primary medium to showcase portfolios, establish emotional connections with potential clients, and expand service visibility. The research employs a descriptive qualitative method, utilizing data collection techniques such as observation of the @seatapwedding account and a literature review related to digital communication and branding. The results indicate that the company utilizes several approaches, including visual style consistency, storytelling in messaging, direct audience interaction, and the optimization of Instagram features to strengthen brand identity. Furthermore, client testimonials and collaborations with various vendors enhance public trust in the services offered. The impact of this research demonstrates that an integrated visual communication strategy effectively transforms social media from a mere portfolio gallery into a powerful tool for public trust conversion and brand legitimacy within the competitive wedding industry. Practically, these findings provide a strategic reference model for creative service providers to optimize digital platforms for building emotional resonance and long-term reputation. This study also contributes to the development of digital communication literature regarding the significance of emotional branding in establishing the credibility of service-based companies. Key Words: Communication Strategy, Branding, Instagram, Wedding Organizer, Digital Reputation